Leg-Length Discrepancy, Functional Scoliosis, and Low Back Pain. Issue 8 (August 2018) - Sheha, Evan D.; Steinhaus, Michael E.; Kim, Han Jo; Cunningham, Matthew E.; Fragomen, Austin T.; Rozbruch, S. Robert
Abstract : In the setting of leg-length discrepancy (LLD), functional scoliosis occurs when the lumbar spine compensates for pelvic obliquity to maintain shoulder balance. Long-standing LLD may result in degenerative changes of the lumbar spine, altered gait mechanics, and low back pain. Patients with LLD, low back pain, and functional scoliosis should undergo radiographic evaluation with the pelvis leveled using blocks placed under the shorter limb. When the LLD or symptoms are minimal, patients may benefit from a shoe lift. Patients with an LLD of >20 mm may be considered for operative intervention.